Designing a Midterm Reading Test for Junior High School Students in Semarang: A Practical Experience of a Master Student in TESOL - Waliyadin, Waliyadin (Vision: Journal for Language and Foreign Language Learning, 2019)
Designing a test is an uneasy task. It is proven by the fact that many teachers find difficulties in designing a good test. The present article attempts to review the English school exam in Indonesia and present an example of the test design of a midterm reading test for junior high school students in Semarang. To this end, firstly, a sample of test script of the school exam for JHS students in Semarang in the academic year 2017/2018 was reviewed. The review of the test shows that creating a good quality of test items still become a concern for English teachers as they made some grammatical errors. Consecutively, a midterm reading test was also designed and administered in a junior high school in Semarang, Central Java. Then, the test designed was evaluated by considering the validity, reliability, and practicality as suggested by (Brown Abeywickrama, 2010). Â The administration of the test and evaluation show some weaknesses; therefore, the suggestions for the betterment of the test design are also made, such as revising some test items with a very low facility index and negative discrimination index. This study implicates pedagogically the teachers to train students on how to summarize and paraphrase since these skills underrepresented.